Shear strength of reinforced concrete slender beams - Arslan, G. (ICE PUBLISHING, 2010)
During the last four decades many equations have been proposed to estimate the shear strength of reinforced concrete (RC) beams. However, in terms of accuracy and uniformity of the prediction, there is considerable diversity between existing test results and concrete design code requirements and researchers' predictions. In this study, by considering the size effect of RC slender beams without stirrups, a new design expression is proposed for cracking shear strength. The proposed equation and also other eight different code requirements and researchers' predictions are compared with the test results of 249 beams without stirrups. It is found that the proposed equation shows good agreement with regard to existing test results. Thus, the proposed equation is used for the resistance of concrete to obtain the shear strength of RC slender beams with stirrups. The proposed equation is verified by comparing the results of the existing 248 shear tests carried out with RC slender beams with stirrups covering a wide range of beam properties and test methods.
Keywords: beams & girders; mathematical modelling; strength and testing of materials; QUASI-BRITTLE FRACTURE; DOUBLE-K CRITERION; CRACK-PROPAGATION; PART II; PREDICTION; PERFORMANCE; FAILURE; Construction & Building Technology; Engineering